Exploring Interaction Patterns in EFL Teaching and Learning Context - Sokhira Linda Vinde Rambe (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study talked about interaction patterns in EFL teaching and learning context which aims to explore types of interaction patterns implemented by the teachers, problems faced and solutions done to solve the problems. The problem in this study was formulated into three namely; 1) what types of interaction patterns do the teachers use in teaching English?, 2) What are the problems faced by teachers in applying interaction patterns in teaching English, and 3) How do the teachers solve the problems in implementing interaction patterns in teaching English?. The research in this study was in a form of qualitative descriptive research. This study conducted research toward three qualified teachers at Language Development Center of IAIN Padangsidimpuan together with the students who study English with them. The instruments used were observation and interview. This study found that there were some interaction patterns applied by the teachers in teaching English. They were group work, full class interaction, close ended teachers questioning, open ended teachers questioning, individual work, choral responses, and students initiate and teachers answer. From these interaction patterns, there are two patterns dominantly used by the teachers i.e. group work and full class interaction. Related to the problems of implementing interaction patterns, this study found that teachers got difficulty in monitoring students’ group work and students’ full class activity